How women lead [ 8 essential strategies successful women know - Hadary, Sharon; Henderson, Laura , 1948- (McGraw-Hill, 2013)
Lead like a woman. It's a new world for women in business leadership. Did you know that: Companies with more women in high-level positions report better financial performance than those with fewer women at these levels? 40% of all privately held businesses are owned by women? More than half of all professional and managerial positions are held by women? The number of women earning $100,000 or more has grown at a faster pace than it has for men in the United States? 6.3% of the top earners in the Fortune 500 companies are women? Women are moving into leadership roles in business, government, and the military, and they're gaining positions of increasing stature and higher salaries. But women's upward movement is not matching the rate of their movement into professional and managerial positions. It is time to own your destiny. Gain the confidence and know-how you need to navigate it all. Your roadmap to achieving your aspirations, How Women Lead provides hard-won wisdom from women who have reached truly impressive heights in their careers. Written by two women's leadership experts who are themselves successful leaders, How Women Lead gives women the information they need to become high-potential leaders but don't get in business school: how to build a career on their own terms, gain the critical business management skills needed to advance, and advocate successfully for themselves. Whether you're already in the leadership pipeline, contemplating your next career move, or are working to empower women in business, the lessons of How Women Lead will show you the sky's the limit when you combine women's leadership strengths with sound business acumen. - Publisher